Thiamine-deficiency in the ICU-patient - When the plug is out - Wilfred Druml; Thomas Staudinger; Gunnar Elke (Critical Care, 2026)
Abstract There is a notorious difficulty in judging micronutrient stores and requirements in critically ill patients and deficiency states will be rarely associated with clinical symptoms. A fundamental exception is vitamin B1, thiamine, a micronutrient of crucial importance in mitochondrial energy production. With thiamine deficiency ”the energy plug is out”, resulting in multiple organ dysfunctions, such as of brain, heart, kidney or respiratory system, lactate formation is increased, lactate clearance reduced, all fundamentally affecting the course of disease and prognosis of a patient. Several patient groups, such as malnourished subjects or patients with liver or kidney disease are already deficient prior to hospital or ICU admission, but there is also a high risk of developing deficiency during ICU stay. There are several well defined patient groups at risk, however, there is no need to measure plasma concentrations, as assays are mostly not available, costly and actually do not reflect the cellular status. There is quite solid evidence that thiamine may preserve / improve organ function (brain, heart, kidney), reduce blood lactate concentration and reduce mortality in various groups of critically ill patient. An extra thiamine supplementation should be given in high-risk patient groups, which bears no risk of inducing toxicity and is cheap, so we advocate to administer thiamine whenever a deficiency state is suspected.